GST-4-Dependent Suppression of Neurodegeneration in C. elegans Models of Parkinson’s and Machado-Joseph Disease by Rapeseed Pomace Extract Supplementation - Pohl, Franziska; Teixeira-Castro, Andreia; Costa, Marta Daniela; Lindsay, Victoria; Fiúza-Fernandes, Juliana; Goua, Marie; Bermano, Giovanna; Russell, Wendy; Maciel, Patrícia; Kong Thoo Lin, Paul (Frontiers in Neuroscience, 2019)
Genetic mutations and aging-associated oxidative damage underlie the onset and progression of neurodegenerative diseases, like Parkinson’s disease (PD) and Machado-Joseph disease (MJD). Natural products derived from plants have been regarded as important sources of novel bioactive compounds to counteract neurodegeneration. Here we tested the neuroprotective effect of an ethanolic extract of rapeseed pomace (RSP), a rapeseed (canola) oil production by-product, in C. elegans models of MJD and PD. The extract, containing sinapine and other phenolics, restored motor function of mutant ATXN3 animals (MJD) and prevented degeneration of dopaminergic neurons in one toxin-induced and two genetic models of PD. Whole-organism sensors of antioxidant and xenobiotic response activation revealed the induction of phase II detoxification enzymes, including glutathione S- transferase (GST-4) upon RSP extract supplementation. Furthermore in vivo pharmacogenetic studies confirmed gst-4 is required for the therapeutic effect of RSP extract in the two disease models. The results suggest that GST-4-mediated antioxidant pathways may constitute promising therapeutic co-targets for neurodegenerative diseases and confirm the utility of searching for bioactive compounds in novel sources, including food and agricultural waste/by-products, such as RSP.